HOW INDONESIANS CAN CONTRIBUTE TO THE DEVELOPMENT OF COMMUNICATION THEORIES - Deddy Mulyana (Universitas Padjadjaran, 2004)
This article responds to the concern of some Indonesian communication scholars with the scarcity of “indigenous” communication theories developed by Indonesians themselves. It must be admitted that in our country objective communication theories developed in the West are more dominant than interpretive (phenomenological and critical) ones. This leads to the frequent deductive testing of the existing theories, making our research stagnant. To develop indigenous communication theories, the best solution is to conduct phenomenological (inductive) research on intercultural communication phenomena and critical research on mass communication phenomena (especially television programs) in Indonesia. This will help us to develop Indonesian communication theories as well as to enlighten our society. Keywords: Phenomenological paradigm, objective paradigm (behaviorism and structural functionalism), critical paradigm